How teacher and classmate support relate to students’ stress and academic achievement - Hoferichter, Frances; Kulakow, Stefan; Raufelder, Diana (Frontiers in Psychology, 2022)
According to the conservation of resources theory (Hobfoll & Ford, 2007), social support provides resources to help overcome challenges. Although some empirical findings have emphasized the pivotal role of teacher support and/or peer support for students’ stress and academic achievement, multilevel analyses that consider contextual class and individual student effects are scarce. The current study addresses this gap and further includes gender, socioeconomic status, and neuroticism as covariates. Multilevel analyses in Mplus were conducted. All measures were taken at the student level and then aggregated to the classroom level to estimate class-level relationships. Results revealed that on the individual level teacher support was related to higher ability to cope and lower levels of helplessness, while on the class level, peer support by classmates was related to higher ability to cope and academic achievement. The context effects also show that in classes with higher peer support, students are more likely to benefit in terms of coping ability and achievement, whereas in classes with higher teacher support, students tend to show less coping ability.